Relações entre os estágios do ciclo de vida empresarial, previsão de lucros e custo implícito de capital - Souza Neto, Francisco Alves de (2019)
This study aimed to show the effect of the Theory of Companies' Life Cycle on Profit Forecasting (Chapter 2) and the Implicit Cost of Capital (ICC) in Companies' Life Cycle Stages (CLCS) (Chapter 3). The sample consisted of publicly-traded companies listed on B3 (Brazil, Exchange and Exchange), in addition to the NYSE (New York Stock Exchange), in the period from 2005 to 2011. In Chapter 2, as a theoretical basis, the use of profit forecast model of one, Dijk and Zhang (2012), such as the case of letters, total assets, dividend payments, losses and additions to predict future information. The model consists of interpreting as past information in an attempt to reduce the forecast error margin, without the sense that a ECV variable (DICKINSON, 2011) is introduced, justified by the Theory of Companies Life Cycle that presents an informational power for the behavior prediction. The results found in CLCS ads did not increase profitability, which translates into more subjects in mature companies. The main contribution of chapter 2 to the literature was to show that the Theory of Companies Life Cycle is capable of improving profits, being more evident in mature companies. In Chapter 3, we used the Gordon and Gordon (1997) methodology to extract the ICC with the use of CLCS. Since the CICs were created as a component with an average of three models, with a purpose of absorbing their own specifications and will become a great balance. Subsequently, it was collected as the ICC behaves in each CVD, linked to control variables. It was evidenced that ICC was more important at initials stages, having a higher value at birth and exercise to a maturity stage. One can still relate to the market of companies, market-to-book, dividends payment. The main contribution of chapter 3 to the literature was evidenced by an ICC of behavioral measurement in each CVD.